Experimental validation of bulk-graphene as a thermoelectric generator. (10th May 2021) - Uzair Khan, Muhammad; Naveed, Amir; Ehtisham Gillani, Syed; Awan, Dawar; Arif, Muhammad; Afridi, Shaista; Hamyun, Muhammad; Asif, Muhammad; Tabassum, Saadia; Sadiq, Muhammad; Lais, Muhammad; Aslam, Muhammad; et al.
Abstract: Quest for alternate energy sources is the core of most of the research activities these days. No matter how small or large amount of energy can be produced by utilizing the non-conventional techniques and sources, every bit of innovation can reshape the future of energy. In this work, experimental analysis of the thermoelectric (TE) properties of bulk-graphene in the temperature range of (303 to 363) K is presented. Graphene powder was pressed to form a pellet which was used to fabricate the TE device. The effects of temperature on the Seebeck coefficient, electrical and thermal conductivities, and the dimensionless figure of merit (FOM) were measured. The increasing value of the Seebeck coefficient (thermopower) with temperature is indicant of the metallic behavior. Additionally, the observed thermopower (TEP) is positive, which shows that the majority charge carriers are holes and peaked to a value of 56 μ V K −1 at 363 K. The thermopower of the pellet is four times larger than the previously reported values for single layer graphene (SLG) and few layer graphene (FLG). In addition to this, low values of the thermal conductivity were observed for the pellet which is one of the requirements of a good TE material. Besides this, an upward trend is observed with increasing temperature for FOM, which attains a peak value of 0.0016 at 363 K, which is almost ten times that of the previously reported values.